Studies on the Evaluation of Teratogenic Potential of SSRI (Escitalopram) on Chick Embryogenesis (Gallus gallus domesticus) - Khare, Riya Sandesh; Radkar, Tanvee Vinayak (Journal of Drug Delivery and Therapeutics, 2025)
Escitalopram is a selective serotonin reuptake inhibitor (SSRI) used for the treatment of depression, anxiety and panic disorders. The purpose of this study is to examine the effect of Escitalopram on the early developmental stages of chick embryo Gallus gallus. Escitalopram’s teratogenic potential was further assessed using YSM analysis and protein biochemistry. The treated embryos showed mild to severe teratogenic effects at 5mM and 10mM dose respectively. Enzyme Assay was conducted to see whether the drug treatment interfered with the cellular pathways. The levels of Alkaline phosphatase (ALP) and Acetylcholinesterase (AChase) were found to be reduced in the treated embryos. YSM Assay reveals that in ovo drug administration has an impact on the angiogenesis of the embryo. In depth further studies are needed to understand the long-term effects of Escitalopram on the developing embryos at cellular and molecular level so as to take caution while prescribing the drug during pregnancy.Keywords: Gallus gallus domesticus, Enzyme Assay, Escitalopram, Teratogenesis, Yolk Sac Membrane (YSM) Assay, Protein Biochemistry.